Strategies for the Isolation and Identification of Gastric Cancer Stem Cells - Jianhua Wang; Jie Qu; Qiang Hou; Xueping Huo; Xiangrong Zhao; Le Chang; Cuixiang Xu (Stem Cells International)
Gastric cancer stem cells (GCSCs) originate from both gastric adult stem cells and bone marrow cells and are conspicuously present within the histological milieu of gastric cancer tissue. GCSCs play pivotal and multifaceted roles in the initiation, progression, and recurrence of gastric cancer. Hence, the characterization of GCSCs not only facilitates precise target identification for prospective therapeutic interventions in gastric cancer but also has significant implications for targeted therapy and the prognosis of gastric cancer. The prevailing techniques for GCSC purification involve their isolation using surface-specific cell markers, such as those identified by flow cytometry and immunomagnetic bead sorting techniques. In addition, in vitro culture and side-population cell sorting are integral methods in this context. This review discusses the surface biomarkers, isolation techniques, and identification methods of GCSCs, as well as their role in the treatment of gastric cancer.